2015
DOI: 10.1089/apc.2015.0079
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Apnea Symptoms as a Predictor of Fatigue in an Urban HIV Clinic

Abstract: Fatigue is common among persons living with HIV (PLWH), and risk factors for obstructive sleep apnea (OSA) such as older age and obesity are increasingly prevalent. Studies of OSA among PLWH are lacking, so we aimed to characterize OSA symptoms and associated clinical consequences (e.g., fatigue) among a contemporary population of PLWH. Self-administered surveys containing 23 items that included self-reported snoring, witnessed apneas, estimated sleep duration, the Epworth Sleepiness Score (ESS), and the FACIT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
3
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 47 publications
(45 reference statements)
2
8
3
1
Order By: Relevance
“…In our study, participants who had anemia had approximately five times higher risk for developing fatigue than those without anemia which is in line with the studies done in the USA [38] and China [31]. Anemia is a wellknown reason for fatigue.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study, participants who had anemia had approximately five times higher risk for developing fatigue than those without anemia which is in line with the studies done in the USA [38] and China [31]. Anemia is a wellknown reason for fatigue.…”
Section: Discussionsupporting
confidence: 90%
“…This consistent result can be explained by the use of large sample size, similarities in study population and similarities in eligibility criteria. On the other hand the prevalence in our study was lower than the finding of other studies done in South Africa, 66.7% [9], United Kingdom (UK), 65.1% [17], Uganda (61%) [38], and China, 86.8% [31]. This discrepancy could be due to difference in study criteria, for example, the study in South Africa used study-subjects who were extremely ill and the other two studies (Uganda and the UK) used participants who developed at least two HIV-related symptoms, which may increase the prevalence of fatigue.…”
Section: Discussioncontrasting
confidence: 88%
“…On the other hand the prevalence in our study was lower than the finding of other studies done in South Africa, 66.7% [9], UK, 65.1% [17], Uganda (61%) [38], and China, 86.8% [31]. This discrepancy could be due to difference in study criteria, for example, the study in South Africa used study-subjects who were extremely ill and the other two studies (Uganda and UK) used participants who developed at least two HIV-related symptoms, which may increase the prevalence of fatigue.…”
Section: Discussioncontrasting
confidence: 88%
“…In this study, the key predictors that were signi cantly associated with fatigue among HIV/AIDS adults were clinically diagnosed anemia, low income, parity, and living without a spouse. Likewise, studies done in the USA and China reported an association between fatigue and anemia [42,44,45]. Fatigue is the cardinal symptom of anemia, a prognostic marker of disease progression, and frequently reported as a predictor of morbidity and mortality among HIV/AIDS patients.…”
Section: Discussionmentioning
confidence: 99%